Універсальний координатний гаусоїдний базис для розрахунку зв’язаних станів систем декількох частинок - Gryniuk, O.B.; Grinyuk, B.E. (Publishing house "Academperiodika", 2023)
A new simple basis is proposed for variational calculations of the bound states of a few-particle system. For an N-particle system with pairwise interactions, the matrix elements of the Hamiltonian are found in an explicit form. A modified version of the basis invariant with respect to spatial translations is considered as well. As an example, the 12C nucleus is considered as a system consisting of three α-particles, and the convergence of the method is briefly discussed.